(untitled) (Research, Society and Development, 2021)
This article aims to examine how family farmers in Uruçuí, Piauí, characterized by a heritage of traditional knowledge and practices that adjust to modernity, build their economic reproduction strategies to meet their production and consumption needs, considering that the municipality consolidates itself in the activities of globalized agribusiness, which has caused uncertainties about the future of family farm work. The analysis is based on the ethnographic method, through systemic observations and application of semi-structured interviews with 254 family farmers, distributed in 17 rural communities in the municipality. The questions involved the use of land, work and relations with the market. It was concluded that family farming in Uruçuí manifested a serious social crisis characterized, above all, by meager financial income and difficulties in accessing rural credit lines, prejudicing the family production, impacting the supply economy and pluriactivity.